Ultrasonographic abnormalities of wrist and metacarpophalangeal joints in a cohort of Egyptian patients with systemic lupus erythematosus - Noha H Shedid; Eman A Hafez; Safa A Akram; Hossam M Sakr; Elham S Mohamed (SpringerOpen, 2019)
Background Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by chronic inflammation and autoantibodies, affecting different organs. Musculoskeletal manifestations are one of the most common manifestations in SLE, usually nonerosive and nondeforming. Musculoskeletal ultrasonography (US) can detect synovial inflammation and structural damage lesions. Aim The aim was to detect ultrasound abnormalities of the wrist and metacarpophalangeal (MCP) joints in a cohort of Egyptian patients with SLE and their relation to disease activity. Patients and methods A total of 80 female patients with SLE and 10 age-matched apparently healthy controls were enrolled. Clinical examination and laboratory investigations were done for all patients. US examinations of both wrists and second to fifth MCP joints were done for all participants. Patients were divided according to clinical and US assessments. Results US detected synovitis of MCPs and/or wrist in 63.75% patients compared with 10% of healthy control (P<0.01). Synovitis was identified in most of the patients with SLE who had hand arthralgia when compared with patients without (P<0.01). Conversely, 18.3% of patients had wrist joints tenderness on physical examination with no sonographic abnormalities. Systemic Lupus Erythematosus Disease Activity Index score and dsDNA antibodies were associated with the presence of synovitis. Conclusion US is a valuable tool for assessment of joints in patients with SLE. It helps in detection of inflammation when compared with clinical examination and monitoring disease activity.